Consumers' knowledge, attitudes, and usage of electronic banking technologies - Sabri, Mohamad Fazli; Lee, Mei Cher (Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan & Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2011)
In Malaysia, e-banking represents a relatively small portion of customers compared to the United States (US) where more than 30 billion households own PCs to manage their financial affairs. The main obstacle to the acceptance of e-banking in Malaysia is the lack of market awareness. This indicates that the levels of knowledge among consumers towards electronic banking are still low. According to the research that has been done by Curran and Meuter (2005) in US, 95 percent of the respondents knew that their bank offered Automated Teller Machine (ATM) services, only 59 percent knew that transactions can be conducted over the phone, and only 48 percent were aware of online banking as an alternative. The most worrisome is that 11 percent belived that their bank did not offer online banking and seven percent indicated that their bank did not offer banking facilities by phone when, in fact, the bank did offer those services. The circumstance is even worse in a developing country like Malaysia if a developed country like the US, faced it too.